KAJIAN SNI 01-2886-2000 MAKANAN RINGAN EKSTRUDAT - Devi Ambarwaty Oktavia (JURNAL STANDARDISASI, 2007)
Extruded snack are a product that produce from a tools call extruder by high temperature and short time. Standard quality of extruded snack which required on SNI 01-2886-2000 has not listed odor, taste and colour quantitatively. SNI 01-2886-2000 has not listed yet protein content, calcium content, zinc and total dietary fiber. Improving Indonesian standard for extruded snack advised then the quality of extruded snack will be better. In order to improve Indonesian standard of extruded snack, listing odor, taste and colour quantitatively, protein content, calcium content, zinc, and total dietary fiber as quality atribute on SNI of extruded snack needs others comprehensive researches.